Here's the question you clicked on:
ethompsonn
Solve for x. 3(3x - 1) + 2(3 - x) = 0 x = 3/7 x = -3/7 x = 1/3 x = -1/3
3(3x - 1) + 2(3 - x) = 0 9x - 3 + 6 - 2x =0 whats next
8x = -3 | : 8 x = -(3/8) correct me if I'm wrong :)
help her walk through the problem
9x - 3 + 6 - 2x =0 7x + 3 =0 7x = -3 x = -3/7
@addinol Two things. 1. Please don't interrupt other users trying to work with an asker and just provide the answer. It's considered rude and won't be tolerated here. 2. Please try and guide the asker through the problem instead of just giving the answer. Thanks.
Okay, sorry, I'm new here :) By the way, ups I somehow got 8 from 9-2 :D